HOW TO COPE WITH COVID-19: GLOBAL HEALTH AND ECONOMIC CRISIS - Bushra Naureen; Mehmood Asghar (International Journal of Pharmacy & Integrated Health Sciences)
In December 2019, the first coronavirus (COVID-19) outbreak was reported in Wuhan City, Hubei, China, and spread like wildfire, in a matter of days, throughout the globe. The COVID-19 common signs include pneumonia-like symptoms (shortness of breath, chest pain) along with fever and dry cough, which are closely associated with severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS). COVID-19 pandemic, like the Spanish and Swine flu, is a global health crisis concerning morbidity, mortality, and health emergency (1). The contagious and infectious nature of the COVID-19 pandemic has converted this health catastrophe into a global economic crisis as well. This is because underdeveloped countries have limited resources to provide healthcare facilities to the entire affected population. Thus, breaking the chain of COVID-19 spread via lockdown (along with timely testing, quarantine, and social distancing) is the best option to control the pandemic (2). A lockdown is one of the ways to prevent the chain of COVID-19 transmission. However, it may not be a feasible option, especially for countries like Pakistan, where it serves as it puts further pressure on the already struggling economy.